HUBUNGANANTARABUDAYAKERJADANMOTIVASI KERJA TERHADAP KINERJA GURU DI SMP IT INSAN ROBBANI KECAMATAN KOTABUMI SELATAN KABUPATEN LAMPUNG UTARA - KARTIKA RATNA DEWI; Nurul Hidayati Murtafiah; Rahmat Hidayat (UNISAN JURNAL, 2024)
Work culture is a set of behavioral patterns that are inherent in the whole of every individual in an organization. Work culture differs from one organization to another, this is because the behavioral foundations and attitudes reflected by each person in the organization are different. The method used in this research is a relationship method, namely a type of research that attempts to reveal whether there is a relationship between the predictor variable (independent variable) and the response variable (dependent variable). In this research, work culture and work motivation are the independent variables and teacher performance is the dependent variable. The results of the relationship test between variables show that there is a strong relationship between work culture and teacher performance at SMP IT Robbani Kecamatan Kotabumi Selatan Kabupaten Lampung Utara, with a significance level of 5%. Teacher motivation and teacher performance at SMP IT Robbani Kecamatan Kotabumi Selatan Kabupaten Lampung Utara have a moderate and sufficient relationship, with a significance level of 5%. Meanwhile, work culture and teacher motivation together with teacher performance at SMP IT Robbani Kecamatan Kotabumi Selatan Kabupaten Lampung Utara have a strong relationship, with a significance level of 5%. Keywords:Work Culture and Work Motivationon Teacher Performance